Genome-wide association study of bronchopulmonary dysplasia: a potential role for variants near the CRP gene - Mahlman M; Karjalainen MK; Huusko JM; Andersson S; Kari MA; Tammela OKT; Sankilampi U; Lehtonen L; Marttila RH; Bassler D; Poets CF; Lacaze-Masmonteil T; et al. (NATURE PUBLISHING GROUP, 2022)
Bronchopulmonary dysplasia (BPD), the main consequence of prematurity, has a significant heritability, but little is known about predisposing genes. The aim of this study was to identify gene loci predisposing infants to BPD. The initial genome-wide association study (GWAS) included 174 Finnish preterm infants of gestational age 24-30 weeks. Thereafter, the most promising single-nucleotide polymorphisms (SNPs) associated with BPD were genotyped in both Finnish (n = 555) and non-Finnish (n = 388) replication cohorts. Finally, plasma CRP levels from the first week of life and the risk of BPD were assessed. SNP rs11265269, flanking the CRP gene, showed the strongest signal in GWAS (odds ratio [ OR] 3.2, p = 3.4 x 10(-6)). This association was nominally replicated in Finnish and French African populations. A number of other SNPs in the CRP region, including rs3093059, had nominal associations with BPD. During the first week of life the elevated plasma levels of CRP predicted the risk of BPD (OR 3.4, p = 2.9 x 10(-4)) and the SNP rs3093059 associated nominally with plasma CRP levels. Finally, SNP rs11265269 was identified as a risk factor of BPD (OR 1.8, p = 5.3 x 10(-5)), independently of the robust antenatal risk factors. As such, in BPD, a potential role for variants near CRP gene is proposed.